Analysis of Fishing Community Sustainability and Policy Scenario based on Sustainability Leverage Factors in Indonesia - Mirajiani; Asep Hamzah; Siti Widiati (Migration Letters, 2023)
Sustainable communities combine ecological, economic and social aspects of people’s lives and pay attention to sustainability in the future. This study aims to explore how the sustainability of fisherman communities is posited in the framework of sustainable coastal development in Indonesia. This study used a mixed data collection method (including both qualitative and quantitative methods). The mixed method included observation, in-depth interviews and focus group discussions, structured interviews, and survey techniques. Quantitative data were analyzed using RAPFISH software and strengthened by the MONTE CARLO test. The results of the research showed that the economic dimension played an important role in the sustainability of fishing communities. However, it required a balance from other dimensions. The ecological dimension had a sustainability value in the poor category, which was 46.5, based on the value, ecologically, various efforts are necessary so that the fishery activities in Banten coastal areas can be sustainable. The economic dimension was in a good category, with a sustainability status value of 80.93, while the social dimension was in a fair category with a sustainability status value of 65.8. Sustainability status on the technology dimension was in a fair category, with a value of 62.22. On the institutional dimension, the value of sustainability status was 63.1 in a fair category. Community sustainability can still be improved by paying attention to leverage factors in each dimension. Policy scenarios based on sustainability leverage factors have been successfully formulated in accordance with the leverage factors of the economic, ecological, social, technological and institutional dimensions.